Wilting of bean plants from tobacco mosaic virus from smoking tobacco in Pakistan - Iftikhar, Yasir; Vadamalai, Ganesan; Sajid, Ashara; Mubeen, Mustansar; I. Ullah, Muhammad (Pharmaceutical and Biological Society, 2018)
Tobacco mosaic virus (TMV) was detected in one out of three samples of different commercial brands of cigarettes by RT-PCR. A PCR product between 650-680bp in size was observed on 1% agarose gel, which was confirmed as TMV through sequencing. Mechanical inoculation of sap from the PCR positive samples showed local lesions on bean (Phaseolus vulgaris) plants used as an indicator plant. In addition, symptoms of wilting were also observed in the bean plants. RT-PCR of extract from the inoculated bean plants reconfirmed the presence of TMV in bean plants. This study shows that TMV can be prevalent and has virulence in commercial tobacco (Nicotiana spp.). The wilting in bean plants upon mechanical inoculation of TMV was observed for the first time and can be reported as a new symptom of TMV infection in beans. This wilting associated to TMV opens the discussion for presence of different isolates of virus, symptomatic expression on differential hosts and methods of mechanical inoculation.